University management system in system-z mainframe (zMS) - Nallavadu, Asha Rani (2012)
Ability to perform multiple tasks simultaneously 24/7 is very essential in order to maintain a system‘s integrity and accessibility.University Management System in System-z Mainframe(zMS)is information management system done in the mainframe environment for the system operators to create a batch type input and output system.The system is designed using System-z as the operating system,to ease the tasks of the system operator to browse for records and view it in a formatted file.It will make use of the logical partition of a mainframe,to run the managerial operations.This report will discuss on the preparation, analysis, development and discussion based on the development cycle of this system.A complete reference and research details have been furnished in this document. This document will be a quick reference to refer on the specification and requirements of the system.